2018
DOI: 10.1080/02109395.2017.1407902
|View full text |Cite
|
Sign up to set email alerts
|

Neurodynamics inside therapeutic interaction: a case study with simultaneous EEG recording / La neurodinámica en el contexto de la interacción terapéutica: un estudio de caso con una grabación simultánea de EEG

Abstract: Recent research on processes of psychotherapy has focused on the study of patient-therapist regulation. Evidence concerning verbal and nonverbal coordination as predictors of therapeutic alliance and outcome in psychotherapy has been cumulating. These, along with others results in the field of social neuroscience, suggest that behavioural coordination may have neurophysiological correlates, which play a role in the regulatory process in psychotherapy.Here we introduce an observational paradigm and analytic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 32 publications
0
14
0
2
Order By: Relevance
“…In support of this idea, Rodríguez et al ( 2018 ) have measured therapist's and patient's EEG potentials along therapeutic sessions and found that there is more activation in the prefrontal cortex of the therapists during advanced periods of the process than at the beginning of the therapy. They suggest that emotional support is greater during the first sessions whereas reflective activities are more common in later stages.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In support of this idea, Rodríguez et al ( 2018 ) have measured therapist's and patient's EEG potentials along therapeutic sessions and found that there is more activation in the prefrontal cortex of the therapists during advanced periods of the process than at the beginning of the therapy. They suggest that emotional support is greater during the first sessions whereas reflective activities are more common in later stages.…”
mentioning
confidence: 98%
“…We believe that in giving a compelling account of how alliance is constructed, in addition to synchrony, we should also study phenomena at different timescales along therapeutic processes, laborious though such a study may be. Regardless of the clinical approach used, therapeutic processes encompass a diversity of therapeutic phases in which different relational patterns predominate (Searles, 1961 ; Westerman et al, 1995 ; Morán et al, 2016 ; Orsucci et al, 2016 ; Rodríguez et al, 2018 ). There might be, for instance, an alliance building phase, an emotional support phase, a narrative phase, and so forth.…”
mentioning
confidence: 99%
“…A simple example could be drawn using psychotherapy research. Hyperscanning electroencephalography (EEG) can be recorded throughout and during psychotherapeutic interactions (Rodríguez et al, 2018) along with other measures (e.g. body movements as in Tschacher et al, 2014; or electrocardiography (ECG) in Watanabe et al, 1996, among others).…”
Section: A Fourth Wave Of Complexity?mentioning
confidence: 99%
“…Even though a considerable technical and analytical gap still exists, acquisition of brain/body dynamics during real-world situations (e.g. Nann et al, 2019;Piñeyro Salvidegoitia et al, 2019;Rodríguez et al, 2018;Zink et al, 2016) as well as in virtual, modified, and/or extended laboratory settings has been -in many cases-successful (e.g. Djebbara et al, 2019;Gramann et al, 2010;Jungnickel & Gramann, 2016;Soto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…La psicoterapia en un contexto altamente ecológico donde un terapeuta se reúne con un paciente para desarrollar una relación profesional que conlleva interacciones de carácter terapéutico. En Chile, esta aproximación se ha utilizado para estudiar el proceso psicoterapéutico (Krause et al, 2007;Martínez, 2011) y en conjunto con EEG para explorar dinámicas cerebrales asociadas Rodríguez et al, 2018).…”
Section: Grabaciones Audiovisualesunclassified